Persistent identifier systems´ maturity: opportunities in the Spanish context - Marín-Arraiza, Paloma (Anuario ThinkEPI, 2022)
Well-established Persistent Identifiers (PIDs) form a trusted basis for open science. They help to ensure that the entities they refer to are discoverable, accessible, Assessable, Intelligible, Useable, Interoperable. After introducing the role of persistent identifiers in the research infrastructure and in the FAIRification process, different PID systems and their maturity levels are described. Finally, opportunities in the Spanish context are discussed.